Neurological deficit following spinal anaesthesia for caesarean section: an anesthetist’s nightmare - Asthana, Unnati; Aggarwal, Deepika; Prakash, Jai; Gupta, Madhu; mali, Anshu (International Journal of Research in Medical Sciences, 2017)
Neurological deterioration after regional anaesthesia, though extremely rare has been reported worldwide. A number of mechanisms like intraspinal hematoma, meningitis, cauda equina syndrome, etc. have been attributed to this dreadful complication. We present a case of a 26 year old female with no past medical history who was posted for emergency caesarean section. After an uneventful surgery under a subarachnoid block, the patient was discharged on the third day. However, on tenth postoperative day, the patient presented in casualty with bilateral lower limb weakness and backache. What was initially thought of being a rare post-operative complication of spinal anaesthesia was found to be an incidental intradural lesion on subsequent evaluation. Even a thorough pre-anaesthetic checkup may not prevent the occurrence of such incidents postoperatively.